Towards Better Understanding of the Pathogenesis of Neuronal Respiratory Network in Sudden Perinatal Death - Mehboob, Riffat; Kabir, Mahvish; Ahmed, Naseer; Ahmad, Fridoon Jawad (Frontiers in Neurology, 2017)
Sudden perinatal death includes the victims of Sudden Infant Death Syndrome, Sudden Intrauterine Death Syndrome and stillbirth; mostly the cause of the death remains unestablished. All over the world, a small number of researchers, in few countries are working in this area, despite the fact, that these sudden demises put a huge emotional setback to the grieved families. Most of these studies are reported from Italy, highlighting the prone sleeping position and smoking as the main etiological factors. Other factors may include prematurity, male gender, lack of breasfeeding, respiratory tract infections, use of pacifiers, infant botulism, extensive use of pesticides or any insecticide etc. However, the causative factors may vary across the globe, if extensive studies are carried out in other countries. Previous studies confirm the widely-accepted hypothesis that neuropathologies of brainstem are one of the main causes of sudden perinatal death. This review is an effort to summarize the findings of the neuropathological evaluation of the brainstems and their association to sudden perinatal death. These abnormalities in brainstem nuclei may disturb the sleep arousal cycle, alter the breathing rhythms, cardio-respiratory functions and ultimately leading to death. Brainstem nuclei in vulnerable infants undergo certain abnormalities that may alter the cardio-respiratory control and culminate in death. This review will enable to get an updated picture of the roles of different brainstem nuclei, their pathologies and the established facts in this regard in terms of its link to such deaths. It will also help to understand the role of brainstem nuclei in controlling the cardio-respiratory cycles in sudden perinatal death and may provide a better understanding to resolve the mystery of these deaths in future. It is also suggested that a global initiative to deal with perinatal death is required to facilitate the diagnosis and prevention in developed as well as in developing countries.